Nghị quyết bầu Tổng Kiểm toán Nhà nước nhiệm kỳ 2021 - 2026 (Nghị quyết số: 07/2021/QH15) - Quốc hội (2021)
Toàn văn Nghị quyết bầu Tổng Kiểm toán Nhà nước nhiệm kỳ 2021 - 2026 (Nghị quyết số: 07/2021/QH15)